A Method of Characterizing the Filling Power of Cut Tobacco Through the Cigarette Maker Parameters. Issue 2 (June 2019) - Yuliang, Li; Shuai, Yang; Lihong, Zhang; Qiang, Zhu; Yucan, Qiu; Ming, Li
Abstract: Filling power is one of the important parameters to characterize the physical structure of cut tobacco. At present, the detection method of cut tobacco filling power cannot reflect the true filling power value of tobacco in real time and accurately, so an intelligent online filling power detection method of the cigarette machine is designed. According to the mechanical position of the suction forming part and the position parameters of the suction belt of the cigarette maker, the linear regression relationship between simulated filling power value and standard filling power value was obtained, the regression relation is applied to the cigarette manufacturing process, then calculate filling power value of cut tobacco in real time. This method has the following advantages:1. in real time;2. reflecting the abnormality of tobacco structure in the cigarette manufacturing process when the filling power exceeds a certain range;3. realizing the linkage between the change of cigarette cut tobacco structure and the physical indicators of cigarettes, then guaranteeing the stability of mainstream smoke chemical indicators and sensory intrinsic quality.